The Bolsheviks and the Red Army, 1918-1922 - Benvenuti, Francesco 1949- (Cambridge University Press, 1988)
The emergence of the military agency of the Soviet state is a crucial but neglected aspect of inter-war Soviet history, and in this pioneering study Francesco Benvenuti provides a detailed analysis of the politics (as opposed to the operational activities) of the Red Army during the Civil War. Several historians have suggested that the roots of Stalinism may be found in the Bolshevik experience during the Civil War, and Benvenuti shows that the military opposition inside the party was much stronger than conventionally supposed: Trotsky's subsequent political weakness owed much to his ruthless pursuit of military goals not always in direct harmony with party interests, as did his technocratic attempts to extend the role of specialist advisers at the expense of party officials
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Soviet Union / Raboche-Krestʹi͡anskai͡a Krasnai͡a Armii͡a / History; Rossijskaja social-demokratičeskaja rabočaja partija (bolʹševikov); Geschichte 1918-1922; Geschichte; Bürgerkrieg; Militär; Sowjetunion; Soviet Union / History / Revolution, 1917-1921